Edible Coating from Banana Peel Waste to Extend Tomato Shelf Life - Sigiro, Oktavia N; Elysapitri, Elysapitri; Habibah, Nur (AGRITEKNO: Jurnal Teknologi Pertanian, 2022)
Kepok banana has been widely used as processed food by the community. The utilization of climacteric fruit is still limited to the use of fruit flesh. The banana peel, which still contains beneficial components like pectin, will therefore be wasted. In this study, pectin from banana peels is processed into an edible coating which will be used as a coating that will be applied to tomatoes. This objective of the study was to determine the best pectin extraction temperature which ranged from 70°, 80°, to 90℃ and the effect of edible coating of pectin extracted from kepok banana peel on the shelf life of tomatoes. Observation of the shelf life of tomatoes was carried out by observing weight loss and vitamin C content in tomatoes. The pectin extraction process and physiological characteristics of tomatoes were studied quantitatively for this study, and the physical characteristics of tomatoes were studied qualitatively throughout the course of 21 days. Based on the results of research on pectin extraction, a temperature of 90°C was discovered to be the best temperature for pectin extraction compared to temperatures of 70° and 80°. At 90℃, the amount of pectin produced was about 2.98%. Based on observations of fruit weight loss and vitamin C content in tomatoes, research on the shelf life of tomatoes revealed that edible coatings had no significant effect on fruit weight loss or vitamin C content. The results of observations of tomatoes at a temperature of 27℃ showed that vitamin C content of tomatoes coated with edible coating decreased by 6.1%, while at a temperature of 10℃, vitamin C content of tomatoes with edible coatings increased by 1.8%.